A space syntax approach to sustainable design for public spaces in historic cities - Yanming Zhu; Lue Huang; Cheng Xie; Weiwei Chen (PLoS ONE, 2026)
Historic cities, as carriers of urban culture and history, have spatial organizations and usage patterns that directly impact district vitality and sustainability.Addressing the common problems in historic cities of disconnection between public space functions and resident needs, along with insufficient spatial flexibility, this study takes Meizhou Ancient City in Guangdong, China, as an empirical case. It introduces space syntax theory to explore sustainable design pathways. This theory can effectively reveal the strengths and weaknesses of spatial structures. Combined with field research, it constructs data models to quantitatively analyze indicators such as integration, spatial symbiosis, and intelligibility, diagnosing core problems: single-function spaces, weak road network connectivity, and chaotic spatial cognition. Based on this, it proposes a strategy of “Inventory Integration–Functional Reconstruction Interface Optimization”. The results show that after the intervention, the spatial symbiosis and ecological resilience of the ancient city were simultaneously enhanced, contributing to the sustainable development of historic cities. The research validates the scientific supporting role of space syntax theory in the design of public spaces for historic cities. The proposed strategy can effectively buffer disturbances from evolving social demands during the development of historic cities, promoting their sustainable and positive development, and providing a reference paradigm for the renewal of similar commercial-residential mixed historic cities.